Temperature Control of Evaporative Cooler (EC) for Converter Dry Dedusting - Li Fangwei; Wang Zhenqing (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
The converter dry dedusting is more complicated with higher requirements in automatic control than the wet dust extraction. The key difficult point is the EC temperature control. This paper puts forth a method to effectively deal with the fluctuated-drastically temperature caused by control lagging at the EC outlet in the traditional converter dry dedusting. The EC outlet temperature can be under control of technological requirement by combining controls of proportion, empirical value, fuzziness and PID. The intelligent system is available with parameter auto tuning, which facilitates the on-site debugging greatly for operators. The result of the on-site application suggests that this method can be used to well handle some technological difficulties in the EC temperature control. DOI: http://dx.doi.org/10.11591/telkomnika.v11i9.3297